Thermodynamic calculation of phase equilibria in stainless steels - Klancnik, Grega (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
In this paper two examples of thermodynamic investigation of stainless steels using both, experimental and modeling approach are described. The ferritic-austenitic duplex stainless steel and austenitic stainless steel were investigated using thermal analysis. The complex melting behavior was evident for both alloy systems. Experimentally obtained data were compared with the results of the thermodynamic calculations using the CALPHAD method. The equilibrium thermal events were also described by the calculated heat capacity. In spite of the complexity of both selected real alloy systems a relative good agreement was obtained between the thermodynamic calculations and experimental results.Key words:CALPHAD, Stainless Steel, Phase diagram, Computational Thermodynamics